A narrative review of Achilles tendon ruptures in racket sports - Larsson, E.; Brorsson, A.; Carmont, M. R.; Fahlström, M.; Zeisig, E.; Nilsson-Helander, K. (International Journal of Racket Sports Science, 2022)
This review aims to enlighten the existing research about Achilles tendon ruptures (ATR) in racket sports. Further, this review will also include the acute management, rehabilitation, treatment and prognosis of an ATR. ATR is a common injury among individuals playing racket sports. However, the literature is limited and not up to date. Previous research claims that up to 70 percent of all ATR is related to sports activities where racket sports dominate. A large number of patients sustaining an ATR return to sport within a year from injury.